The Phlaeothrips-lineage of fungus feeding thrips (Thysanoptera: Phlaeothripidae) in Iran with a new species of Hindsiothrips - Minaei, Kambiz (Zootaxa, 2013)
Hindsiothrips sisakhti sp. n. is described from leaf litter in Iran, this being the first record of the genus from this country. A key is provided to the seven Phlaeothripinae genera recorded from Iran that are considered members of the Phlaeothrips-lineage, in which most species are fungus feeding: Aleurodothrips, Hindsiothrips, Hoplandrothrips, Hoplothrips, Idiothrips, Phlaeothrips and Stictothrips. Structural variation in the group is discussed briefly, and Idiothrips ficus Bhatti is considered a new synonym of Idiothrips bellus Faure.